Diagnostic, Therapeutic, and Prognostic Value of the m6A Writer Complex in Hepatocellular Carcinoma - Gu, Zongting; Du, Yongxing; Zhao, Xueping; Wang, Chengfeng (Frontiers in Cell and Developmental Biology, 2022)
Hepatocellular carcinoma (HCC) has poor prognosis and is usually diagnosed only at an advanced stage. Identification of novel biomarkers is critical to early diagnosis and better prognosis for HCC patients. N6-methyladenosine (m6A) RNA methylation regulators play important roles in the development of many tumors. However, the m6A writer complex, a key executor of m6A methylation modification, has not been independently investigated, and its specific bioinformatics analysis has not yet been performed in HCC. In this study, we used multiple public databases to evaluate the diagnostic, therapeutic, and prognostic value of the m6A writers in HCC. The results showed that expression levels of METTL3, VIRMA and CBLL1 were significantly increased, while expression levels of METTL14 and ZC3H13 were significantly decreased in HCC, which was closely related to clinicopathological factors, such as tumor stage and prognosis. Bioinformatics further explored the possible underlying mechanisms by which the m6A writer complex are involved in activation of tumor-promoting pathways and/or inhibition of tumor-suppressing pathways, including apoptosis, cell cycle, DNA damage response and EMT. Furthermore, we showed that the m6A writer complex is correlated with immune cell infiltration and immunoregulator expression in HCC. In conclusion, the m6A writer complex may represent a promising biomarker and target that can guide targeted therapy or immunotherapy for HCC patients.